Psikoanalsis Tokoh Minato Yukina Dalam Anime Bang Dream Episode of Roselia I: Promise - magnolia magnolia; Ni Wayan Meidariani (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2026)
This study analyzes the character of Minato Yukina in the anime BANG DREAM EPISODE OF ROSELIA I: PROMISE using a psychoanalytic approach. The research focuses on Minato Yukina's ambition to perform at the FWF(Future World Fes) event. Using Sigmund Freud's psychoanalytic theory, the study applies a descriptive qualitative method with a character analysis approach. The data sources include visual clips, dialogues, and the plot of the anime. The analysis shows that Minato Yukina's Id is dominated by the ambitious drive to be the best. Her Ego acts as a mediator, handling this ambition realistically by forming the band Roselia. Meanwhile, her Superego is reflected in the moral and ideal standards she holds, which involve treating music as something serious and dedicated to.